ISLAM BERGERAK DAN PERTARUNGAN GAGASAN: ANALISIS REDAKSI SEBAGAI RESPONS GERAKAN MISIONARIS DAN ZENDING DI SURAKARTA, 1917-1923 M - 'Aini, Luthfah Eta; Maimunah , Siti (Jazirah: Jurnal Peradaban dan Kebudayaan, 2025)
The Missionary and Zending movements that occurred in Surakarta went hand in hand with Dutch colonization in Bumiputra. The establishment of the Church which oversees Christian schools, Christian hospitals, and the publication of Christian newspapers is proof that Missionary and Zending movements was carried out in a very planned manner. In 1917, the newspaper Islam Bergerak was born with the reason of responding to Missionary and Zending movements in Surakarta. The newspaper Islam Bergerak is very interesting to research, because apart from being a tabligh media on paper for Islamic religious groups, the Islam Bergerak newspaper is able to specifically fight against Missionary and Zending movements by publishing ideas of resistance in its editorial. This research uses a historical research method with four stages, namely, heuristics, verification, interpretation and historiography. This research applies the concept of resistance and the concept of Missionary and Zending movements. The approach used in this research is the hermeneutical approach according to Hans Goerge Gadamer. The approach and concept are used to reveal the fact that Missionary and Zending movements and Dutch colonialism are two things that cannot be separated, especially after the implementation of ethical politics in the Dutch East Indies. The development of the newspaper Islam Bergerak shows its dynamism as an Islamic newspaper in the era of movement by containing the idea of ​​resistance to the Missionary and Zending movements phenomenon. The idea of ​​resistance in Islam Bergerak can be categorized into three periods as in this research due to the practice of Missionary and Zending movements which is also experiencing development. Resistance efforts were also accompanied by the establishment of an Islamic religious group so that Surakarta natives would better understand Islamic law.